2021
DOI: 10.3389/fphys.2021.762175
|View full text |Cite
|
Sign up to set email alerts
|

BK Channel Gating Mechanisms: Progresses Toward a Better Understanding of Variants Linked Neurological Diseases

Abstract: The large conductance Ca2+-activated potassium (BK) channel is activated by both membrane potential depolarization and intracellular Ca2+ with distinct mechanisms. Neural physiology is sensitive to the function of BK channels, which is shown by the discoveries of neurological disorders that are associated with BK channel mutations. This article reviews the molecular mechanisms of BK channel activation in response to voltage and Ca2+ binding, including the recent progress since the publication of the atomistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 106 publications
(222 reference statements)
0
22
0
Order By: Relevance
“…We performed a mutational scanning of selected residues on or in the vicinity of the allosteric pathway and found that the mutation T245W reduced, while E219R enhanced the sensitivity of the channel to Ca 2+ for activation 41 7). These results seem to suggest that the pathway through the VSD-CTD interface may make more contributions to Ca 2+ dependent activation.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…We performed a mutational scanning of selected residues on or in the vicinity of the allosteric pathway and found that the mutation T245W reduced, while E219R enhanced the sensitivity of the channel to Ca 2+ for activation 41 7). These results seem to suggest that the pathway through the VSD-CTD interface may make more contributions to Ca 2+ dependent activation.…”
Section: Resultsmentioning
confidence: 92%
“…2d). As summarized in sTable 2, the hydrophobic naphthalenyl group of BC5 was buried in contact with the intracellular side of S0, S1 BK channels are activated by voltage and Ca 2+ with distinctive mechanisms 7,14 . Does BC5 shift the GV relation of BK channels by modulating the mechanism of voltage or Ca 2+ dependent activation?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The activity of these channels is abundantly and functionally distributed in an array of excitable and non-excitable cells. The regulation of such activity can play essential roles in various physiological or pathophysiological events, such as membrane excitability, neurotransmitter release, stimulus-secretion coupling, muscle relaxation, and pain sensation [40][41][42][43][44][45][46]. Moreover, some small molecules, such as BMS-204352, naringenin and QO-40, have been reported to activate I K(M) as well as to enhance the activity of BK Ca channels in excitable cells [9,47,48].…”
mentioning
confidence: 99%